Antropomorfisme Dalam Kesenian Indonesia - Sugihartono, Ranang Agung (Capture : Jurnal Seni Media Rekam, 2011)
Anthropomorphism in arts has been known since the prehistoric period and developed in all over the world, including the primitive arts in the Borneo and Papua hinterland. During the Indonesia-Hindu culture, anthropomorphism was used to represent the character of ‘extraordinary’ in the old fables and serves as a medium of religious. While anthropomorphism in modern Indonesian arts today can be found in the form of comics, movies, and television soap operas although anthropomorphic shape still not as extraordinary as Indonesian-Hindu arts earlier. Key word: anthropomorphism, arts, Indonesia